Infiltration Modeling Using Horton’s Equation on Longbean (Vigna sinensis L.) Cultivation with Organic Fertilizer Treatmen - Konio, Mohamad Arif; Nurmi; Rahman, Rival; Nurdin; Azis, Muhammad Arief (International journal of technology and education research, 2025)
Infiltration, the process by which water enters the soil, plays a crucial role in water availability and fertilization efficiency. This study aimed to determine the effect of organic fertilizer in chicken and cow manures on soil infiltration in long bean cultivation. This research was conducted in Tunggulo Village, Tilongkabila Sub- District, Bone Bolango Regency, Gorontalo Province, from February to April 2025. This study employed a Randomized Block Design with five treatment levels and three repetitions. Infiltration was measured using a double-ring infiltrometer and analyzed using Horton’s model. Based on the analysis, the fertilizer-free treatment (P0) exhibited the highest infiltration capacity with an infiltration rate of 63.37 mm hour-1 and was considered fast according to the Kohnke infiltration classification. Meanwhile, the lowest infiltration capacity was found in the treatment of organic fertilizer in chicken manure with a dose of 10 tons ha-1 (P1), with an infiltration rate of 18.20 mm hour-1 (rather slow). Linear regression analysis revealed a negative relationship between constant infiltration and production, where the constant infiltration factor accounted for only 47.36% of the variation in long bean production, suggesting that excessive infiltration can lead to nutrient leaching from the root zone. The results of the analysis showed that the treatment of organic fertilizer did not have a significant effect on the capacity and rate of infiltration. Based on Horton’s model, the highest infiltration capacity was found in the treatment without fertilizer, followed by the treatment with organic fertilizer from chicken manure at a dose of 20 tons ha-1, and the lowest at a dose of 10 tons ha-1 of cow manure.